Synergy of lignocelluloses pretreatment by sodium carbonate and bacterium to enhance enzymatic hydrolysis of rice straw. (February 2018) - Shen, Zhanhui; Zhang, Kejing; Si, Mengying; Liu, Mingren; Zhuo, Shengnan; Liu, Dan; Ren, Lili; Yan, Xu; Shi, Yan
Graphical abstract: Highlights: A new strategy for lignocellulose pretreatment under mild condition was presented. SNBP significantly enhanced enzymatic hydrolysis of RS. Maximum increase of the sugar release was 31% by SNBP compared to that by NP. The mechanism of SNBP was also elaborated. Abstract: We studied a new strategy for pretreatment of rice straw (RS) to enhance enzymatic hydrolysis under mild condition. This approach uses the synergy of sodium carbonate (Na2 CO3 ) and the bacterial strain Cupriavidus basilensis B-8 (hereafter B-8). After synergistic Na2 CO3 and B-8 pretreatment (SNBP), the reducing sugar yield varied from 335.3 mg/g to 799.6 mg/g under different conditions. This increased by 13–31% over Na2 CO3 pretreatment (284.2–719.2 mg/g) and 3.42–8.15 times over the untreated RS (98 mg/g). Moreover, the composition of RS was changed significantly through decreases in lignin and hemicellulose. We confirmed this change by compositional analysis and physicochemical characterization of the structure of RS before and after pretreatment. We also elaborated a mechanism for SNBP to better explain RS changes and bacterial effects on enzymatic hydrolysis.